Analisis Pengaruh Display Produk Terhadap Keputusan Pembelian pada Usaha Mikro Kecil dan Menengah Donat Madu di Bandung, Indonesia - Hassa, Restu Shofina (International Journal Administration, Business & Organization, 2023)
The purpose of this study was to determine the effect of product display on consumer purchasing decisions of Donat Madu in Bandung and find out how big the influence is. This study uses a quantitative descriptive method, with data collection through the distribution of questionnaires using google form to respondents. The number of respondents is 100 people, with the characteristics of the respondents that have bought Donat Madu products in the city of Bandung. Data processing was carried out using normality test and simple linear regression analysis. The results showed that product display had a positive effect of 31.8% on consumer purchasing decisions of Donat Madu in Bandung. This value is known from the value of R Square (coefficient of determination) in the table of simple linear regression analysis results. From the results of simple regression analysis as well, the correlation coefficient which can be seen from table R is 0.564 and this value is included in the strong category.